Peningkatan Kualitas Supply Chain Material Melalui Teknologi Material Traceability System di PT. Pertamina Gas Eastern Java Area Operation - Dela Agung Septriardy (Journal of Earth Energy Engineering, 2017)
Material Management has always been a major challenge in the world of industry, especially the world of gas transportation. Poor on material planning, limitationon material supply the length of lead time delivery of materials is often a major constraint on the operational productivity. The obligation to maintain the reliability of the instrument to ensure smooth gas supply to consumers remains to be one of the challenges in maintaining productivity. These efforts will not be successful if the company is not able to increase the flexibility of the material supply chain. Not Providing Information Regarding Details Material stock, remoteness Distance Between warehouse and Station, Not Providing Information Details on stock Material, remoteness Distance Between warehouse and Station, and manual data collection worsen the problem tha couldt cause the error on calculating material stock, moreover the problem become more complicated by the lack of collaboration of material information that should be known by the user as the material user on field and planners as a warehouse supervisor. One solution to the problem is to develop the Material Traceabillity Strategy- A technology that can replace manual data entry process that still use paper as a recording media, allows personnel to track and manage the material in real time, Improve Information Sharing among divisions. This paper will discuss the problems and solutions that are applied in order to improve the reliability of materials that can improve supply chain collaboration in the handling of the material. This paper emphasizes the importance of the revolution in material handling in oil & gas transportation company that has been applied and proved successful in PT. Pertamina Gas Eastern Java Operation Area.